2022
DOI: 10.1371/journal.ppat.1010620
|View full text |Cite
|
Sign up to set email alerts
|

Bile acids promote the caveolae-associated entry of swine acute diarrhea syndrome coronavirus in porcine intestinal enteroids

Abstract: Intestinal microbial metabolites have been increasingly recognized as important regulators of enteric viral infection. However, very little information is available about which specific microbiota-derived metabolites are crucial for swine enteric coronavirus (SECoV) infection in vivo. Using swine acute diarrhea syndrome (SADS)-CoV as a model, we were able to identify a greatly altered bile acid (BA) profile in the small intestine of infected piglets by untargeted metabolomic analysis. Using a newly established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 44 publications
(76 reference statements)
1
10
0
Order By: Relevance
“…Integrative analysis of metabolome and proteome data has been proven to be as efficacious strategy to uncover molecular events underlying complex biological processes, and has been utilized in identifying functional proteins and metabolites involved in virus infection [ 13 , 14 ]. Previous studies have reported the proteomic alterations in PEDV-infected IPEC-J2 cells and jejunum derived from PEDV-infected piglets [ 15 , 16 , 17 ], which also detected the differential expression of APOA1, ALB, and TF proteins that were predicted to have interactions in this study. The data indicated the potential functions of these interacted proteins in response to PEDV infection.…”
Section: Discussionsupporting
confidence: 70%
“…Integrative analysis of metabolome and proteome data has been proven to be as efficacious strategy to uncover molecular events underlying complex biological processes, and has been utilized in identifying functional proteins and metabolites involved in virus infection [ 13 , 14 ]. Previous studies have reported the proteomic alterations in PEDV-infected IPEC-J2 cells and jejunum derived from PEDV-infected piglets [ 15 , 16 , 17 ], which also detected the differential expression of APOA1, ALB, and TF proteins that were predicted to have interactions in this study. The data indicated the potential functions of these interacted proteins in response to PEDV infection.…”
Section: Discussionsupporting
confidence: 70%
“…Using pathway enrichment analysis, we found that a lot of metabolic pathways, including amino acid metabolism, TCA cycle, pyrimidine and purine metabolism, lipolysis and ferroptosis were changed significantly in the infected cells, suggesting potential roles of these pathways in virus replication. A previous study conducted untargeted metabolomic analysis in the small intestine of infected piglets and uncovered bile acid (BA) as an important factor in promoting SADS-CoV replication ( Yang et al., 2022 ). Another research revealed that African swine fever virus (AFSV) could modulate lactate production to facilitate its own replication, and inhibitor of lactate dehydrogenase resulted in reduced proliferation of ASFV ( Xue et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The attachment and internalization of PEDV requires cellular cholesterol, and both cellular and viral cholesterol are critical for PDCoV attachment and internalization [ 31 , 32 ]. Furthermore, treatment with the cholesterol depletion reagent methyl-β-cyclodextrin (MβCD) prior to infection diminishes SADS-CoV replication [ 33 ].…”
Section: Important Host Factors Involved In Pecov Replicationmentioning
confidence: 99%
“…Between them, LCA acts through the G protein-coupled receptor-IFN-λ3-ISG15 signaling axis [ 95 ]. However, some bile acids such as cholic acid and CDCA have been shown to promote the replication of PEDV and SADS-CoV [ 33 , 97 ]. Rhodanine derivative LJ001, melatonin, indole, tryptamine and L-tryptophan also restrict PDCoV infection [ 59 , 60 ].…”
Section: Bioactive Compounds With Anti-pecov Activitymentioning
confidence: 99%